Structural, functional and mechanical performance of advanced Graphene-based composite hydrogels - Shokat Hussain; Shrikant S Maktedar (Results in Chemistry, 2023)
Graphene-based composite hydrogels have emerged as promising materials with unique properties due to the incorporation of graphene nanosheets within a hydrogel matrix. This review article presents a comprehensive analysis of the structural, functional, and mechanical properties of graphene-based composite hydrogels. The structural properties of graphene-based composite hydrogels are influenced by the dispersion and alignment of graphene nanosheets within the hydrogel matrix. Various fabrication methods, such as in-situ reduction, physical blending, and chemical crosslinking, have been employed to achieve a well-dispersed and interconnected graphene network. The resulting structures exhibit a high surface area, porosity, and tunable pore size distribution, which are critical for applications such as adsorption, filtration, and catalysis. The functional properties of graphene-based composite hydrogels are primarily attributed to the unique properties of graphene, including its high electrical conductivity, thermal conductivity, & mechanical strength. The incorporation of graphene nanosheets imparts electrical conductivity and promotes electron transfer, enabling applications in sensors, energy storage, and electrochemical devices. Additionally, the high thermal conductivity of graphene enhances heat dissipation, making it suitable for thermal management applications. The mechanical properties of graphene-based composite hydrogels are significantly influenced by the mechanical properties of graphene nanosheets, hydrogel network structure, and interfacial interactions. Graphene reinforcement improves the mechanical strength, stiffness, and toughness of hydrogels, enabling their utilization in load-bearing applications such as tissue engineering scaffolds and wearable devices. Moreover, the graphene-hydrogel interface plays a crucial role in determining the overall mechanical performance of the composite hydrogel. This review discusses recent advancements in the design and fabrication of graphene-based composite hydrogels, highlighting the strategies to enhance their structural integrity, functionality, and mechanical properties. It also provides insights into the relationship between the structure, properties, and performance of these composite materials. Furthermore, challenges and future directions in the development of graphene-based composite hydrogels are outlined, emphasizing the need for scalable manufacturing processes and improved understanding of the underlying mechanisms governing their properties.